ANALISIS IMPLEMENTASI ASEAN CORPORATE GOVERNANCE SCORECARD PADA PERUSAHAAN INDONESIAN TOP 50 PLCS: STUDI DESKRIPTIF KUALITATIF TERHADAP KOMPONEN TATA KELOLA PERIODE 2019–2023 - Sovi Ismawati Rahayu; Sarah Fathiyyah Faatin (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the implementation of the ASEAN Corporate Governance Scorecard (ACGS) in companies classified under the Indonesian Top 50 Publicly Listed Companies (PLCs) during the 2019–2023 period. Using a qualitative descriptive approach through content analysis of annual reports and ACGS score documents from 14 sample companies, this research identifies implementation patterns, score change trends, and variations in governance quality across industrial sectors. The findings reveal that ACGS scores of sample companies generally exhibited an increasing trend from an average of 94.96 points, with Responsibilities of the Board and Disclosure and Transparency being the highest-achieving components, while Rights of Shareholders and Role of Stakeholders still showed significant room for improvement. The banking sector dominated the highest score achievements, while the infrastructure and mining sectors showed greater variation. This study also reveals a gap between high ACGS scores and the actual financial condition of companies, indicating that ACGS implementation remains symbolic-administrative in some companies. These findings provide important implications for regulators, investors, and corporate management in promoting more substantive governance implementation.